2020
DOI: 10.21037/tlcr-20-122
|View full text |Cite
|
Sign up to set email alerts
|

3D radiomics predicts EGFR mutation, exon-19 deletion and exon-21 L858R mutation in lung adenocarcinoma

Abstract: Background: To establish a radiomic approach to identify epidermal growth factor receptor (EGFR) mutation status in lung adenocarcinoma patients based on CT images, and to distinguish exon-19 deletion and exon-21 L858R mutation.Methods: Two hundred sixty-three patients who underwent pre-surgical contrast-enhanced CT and molecular testing were included, and randomly divided into the training (80%) and test (20%) cohort.Tumor images were three-dimensionally segmented to extract 1,672 radiomic features. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 46 publications
2
38
0
Order By: Relevance
“…This approach can be used to determine the molecular type of lung tumors based on the phenotypic appearance in computed tomography (CT) [ 18 ]. Several studies have reported encouraging results in discriminating EGFR mutation using radiomics [ 19 , 20 ]. For example, Jia et al built a random forest classifier to identify EGFR mutation and reached an area under the receiver operating characteristics curve (AUC) of 0.802 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This approach can be used to determine the molecular type of lung tumors based on the phenotypic appearance in computed tomography (CT) [ 18 ]. Several studies have reported encouraging results in discriminating EGFR mutation using radiomics [ 19 , 20 ]. For example, Jia et al built a random forest classifier to identify EGFR mutation and reached an area under the receiver operating characteristics curve (AUC) of 0.802 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are different treatment methods in mutated EGFR group and wild type EGFR group (18), so generally, their prognosis was studied separately. However, many previous studies have shown that radiomic has a high accuracy in distinguishing wild and mutated EGFR NSCLC patients (19,20), therefore, we combined two groups to increase the universality of the models. We also performed subgroup analysis which indicated that the radiomic signature own higher discrimination capacity for wild type EGFR group than mutated EGFR subgroup for all cut-off time points.…”
Section: Discussionmentioning
confidence: 99%
“…Machine-learning-based radiomics are a powerful tool in thoracic oncology, using an exploratory analysis to detect complex patterns that cannot be recognized by traditional analyses. In particular, some publications reported that quantifiable radiomics features extracted from the VOI within CT images can provide more information not only for subtype but also genetic information and immune infiltration of tumors 18 20 . Most cancer cases are subjected to multiple rounds of CT, MRI, and PET-CT prior to thoracotomy, accumulating a large amount of data; however, modern CT, MRI and combined PET-CT units are not standardized for image acquisition and reconstruction protocols.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of radiomics-based machine-learning analyses, several reports have provided new insight into aspects such as the diagnosis of cancer and prognosis prediction 18 20 . Recently, two groups reported that radiomics-based analyses of CT findings could predict the existence of STAS in lung adenocarcinoma 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%